READING AND WRITING SKILLS ANALYSIS OF STUDENTS OF CLASS III SDN 1 LATUKAN - Nova Estu Harsiwi; Tyasmiarni Citrawati; Auliya Niswatul Farichah (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Reading and writing skills should be developed from an early age. Reading and writing skills are language skills that are needed by every individual. Reading and writing skills serve to improve an individual's ability to understand something and increase insight. Based on this, this research was conducted to determine the reading and writing skills of third grade students of SDN 1 Latukan. This study uses a qualitative research design to describe the reading and writing skills of third grade students of SDN 1 Latukan. In this study using interviews and observations to collect data. The results of this study indicate that the reading and writing skills of third grade students are different. This is indicated by 3 students who can read even though they use the spelling method. Then 5 students who can read without using the spelling method even though they are still not fluent. 7 students who are already fluent in reading and 1 student who still can't read at all. While in writing skills as many as 5 students if writing still has to be dictated, then 11 other students are fluent in writing